Efektivitas Jenis Koagulan Poly Aluminium Chloride Menurut Variansi Dosis dan Waktu Pengadukan terhadap Penurunan Parameter Limbah Cair Industri Tahu - Bambang Murwanto (Politeknik Kesehatan Tanjung Karang, 2018)
Tofus industry is a business built in the framework of the development of activities in the field of food that has a positive and negative impact on the environment. The negative impact of the tofus industry in the form of waste disposal that causes pollution problems that damage the environment Pollution environment. The result of solid waste (tofus waste) and liquids waste. Most of the liquid wastes produced by the tofu manufacture industry are viscous liquids that are separated from the clump of tofu called whey. Objective: To determine the effect of Coagulant PAC (Polyaluminium Chloride) with dose of 75 mg / l, 150 mg / l, 225 mg / l, 300 mg / l and slow stirring time 10 minutes, 15 minutes, 20 minutes and 25 minutes in BOD parameters , COD and TSS liquid waste tofu. This type of research is a real experiment with a Pretest-Postest Research with A Control Group Design. this study can be performed using PAC as a coagulant with a dose and slow stirring time which is effective in lowering BOD, COD and TSS levels in tofus wastewater. The research was conducted at Integrated Laboratory of Poltekkes Tanjungkarang and samples were taken were tofus waste in Kelurahan Gunung Sulah Bandarlampung. The population in this study is the tofus waste generated from the tofu industry in Kelurahan Gunung Sulah. Samples taken in this study are liquid waste generated from the tofu industry in Kelurahan Gunung Sulah Bandar Lampung, taken early morning around 09.00 WIB. The results of this study contain an effective compound of administration of Polyalumunium Chloride (PAC), for all parameters of industrial waste know BOD, COD, and TSS, in accordance with Regulation of Minister of Environment No. 5 years 2014 is 765 mg / l, with a stirring time of 25 minutes.